A Comparative Study Of Chinese Words With Different Pronunciation And Polyphonic Pronunciation In Thai Chinese Language Learners - Chinnawat Sripol; Weimin Wang (Universitas Negeri Surabaya, 2024)
The research aimed to analyze Chinese words with varied and numerous pronunciations among Thai Chinese learners. 2) To identify the sources of the problems, we compared single and multiple pronunciations, including varied tones, among Chinese language learners in Thailand, using a documentary research approach based on Scott's principles. The results showed that Thai phonemes replaced Chinese morphemes with Mandarin pronunciations. 2) Using the Roman alphabet for Chinese phonetic forms confuses Thai Chinese students' pronunciation. 3) Some vowels in words mix and change form, resulting in improper pronunciation by students. 4) The pronunciation of tones involves theoretical facts that students must remember. The results of this study will provide a conceptual framework for subsequent empirical research to validate the findings. This data is critical for discovering the underlying reasons for issues among Chinese language learners in Thailand by comparing single and different pronunciations.